1991
DOI: 10.1126/science.252.5010.1300
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Constraints on the Evolution of Egg Size, Number, and Total Clutch Mass in Lizards

Abstract: Proximate constraints on egg size, number, and total clutch mass in side-blotched lizards were examined by experimentally reducing average clutch size from 4.6 eggs to one, two, and three eggs. Eggs from experimentally altered clutches were larger than those from controls, reflecting the trade-off between egg size and number. Moreover, the increased frequency of females with oviducally bound eggs or eggs that burst at oviposition suggests that egg size in clutches with very few eggs are at a functional upper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
147
3
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(159 citation statements)
references
References 21 publications
6
147
3
3
Order By: Relevance
“…Although the question remains open as to what, in turn, limits pelvic girdle dimensions, it is easy to see how selection for, say, locomotor performance, could have ramifying effects on life-history traits. Possibly such patterns of selection are responsible for striking cases of conserved clutch sizes such as that of the Gekkonid lizards, 600 species of which invariably lay two eggs (Stearns 1984), and those of the genus Anolis (anoles), which invariably lay but one (Sinervo and Licht 1991). The important point is that there is no obvious way of distinguishing among the several notions of "constraint" without measuring current and historical patterns of selection, genetic variation, and genetic covariation.…”
Section: The Invocation Of Undemonstrated Constraints On Adaptation Imentioning
confidence: 99%
See 1 more Smart Citation
“…Although the question remains open as to what, in turn, limits pelvic girdle dimensions, it is easy to see how selection for, say, locomotor performance, could have ramifying effects on life-history traits. Possibly such patterns of selection are responsible for striking cases of conserved clutch sizes such as that of the Gekkonid lizards, 600 species of which invariably lay two eggs (Stearns 1984), and those of the genus Anolis (anoles), which invariably lay but one (Sinervo and Licht 1991). The important point is that there is no obvious way of distinguishing among the several notions of "constraint" without measuring current and historical patterns of selection, genetic variation, and genetic covariation.…”
Section: The Invocation Of Undemonstrated Constraints On Adaptation Imentioning
confidence: 99%
“…In morphological traits, such patterns arise as a consequence of development (Arnold 1992;Atchley et al 1992). Sinervo and Licht (1991) experimentally demonstrated complex patterns of selection in lifehistory traits. They showed that the pelvic girdle dimensions of a lizard, Uta stansburiana, impose an upper selective limit to egg size and, since clutch size and egg size trade off phenotypically, a lower selective limit to clutch size.…”
Section: The Invocation Of Undemonstrated Constraints On Adaptation Imentioning
confidence: 99%
“…We used hatchling turtles produced from eggs incubated in a seminatural common environment to eliminate the influence of among-nest environmental variation (e.g., Cagle et al 1993). Similar experimental approaches have proven to be exceptionally useful both in dissecting the evolution of life histories and in evaluating the causes of natural selection (e.g., Reznick et al 1990, Wade and Kalisz 1990, Sinervo and Licht 1991, Sinervo et al 1992, Janzen 1993a, Brodie et al 1995, Dudley 1996, Kingsolver 1996. The results of our study provide insight into the importance of post-emergence offspring mortality in the life history of a longlived organism.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al 1989), mammals (Kaufman & Kaufman 1987) and lizards (Sinervo & Licht 1991a). Clutch size manipulations in birds have long been the prevailing method of studying the consequences of this trade-o¡ (Godfray et al 1991).…”
Section: Introductionmentioning
confidence: 99%